2015
DOI: 10.1111/jgh.12842
|View full text |Cite
|
Sign up to set email alerts
|

Elevated fecal M2‐pyruvate kinase in children with cystic fibrosis: A clue to the increased risk of intestinal malignancy in adulthood?

Abstract: Increased intestinal cell turnover is present in children with PI CF. The lack of relationship between fecal M2-PK and calprotectin suggests that contributing factor(s) other than inflammation may be present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
19
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…This may be, in part, due to previous studies not subcategorising DIOS into complete and incomplete types. Furthermore, the other study to date using the consensus definition did not report their subjects according to gender . The reason(s) for this gender difference is unclear but may be related to greater levels of physical activity including vigorous exercise in men than in women, which in the presence of hot ambient temperatures may result in greater degrees of dehydration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This may be, in part, due to previous studies not subcategorising DIOS into complete and incomplete types. Furthermore, the other study to date using the consensus definition did not report their subjects according to gender . The reason(s) for this gender difference is unclear but may be related to greater levels of physical activity including vigorous exercise in men than in women, which in the presence of hot ambient temperatures may result in greater degrees of dehydration.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the other study to date using the consensus definition did not report their subjects according to gender. 8 The reason(s) for this gender difference is unclear but may be related to greater levels of physical activity including vigorous exercise in men than in women, 21 which in the presence of hot ambient temperatures may result in greater degrees of dehydration. Alternatively, poorer adherence to advice and treatment among men compared with women may be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, M2-PK can be raised in the setting of malignancy [15] and inflammatory states such as inflammatory bowel disease (IBD) [14]. A cross-sectional study previously reported significantly higher fecal M2-pyruvate kinase (M2-PK) levels in children with CF (aged 0 to 18 years) compared to healthy subjects [16]. However in this study there was no correlation between fecal M2-PK and calprotectin levels in the same CF cohort, suggesting other factor(s) may contribute to increased gut cell turnover apart from intestinal inflammation [16].…”
Section: Introductionmentioning
confidence: 99%